Mittlere Schwingungsaniplituden einiger tetragonal-pyramidaler XF₅⁻-Ione - Baran, Enrique José (1973)
Mean amplitudes of vibration for the ions SF₅⁻, SeF₅⁻ TeF₅⁻ and have been calculated from spectroscopic data using an approximation method. The results are briefly discussed, especially in relation with those of isoelectronic species.